Overlap Between Contemporary Art Contexts And Quotation Intertextuality (Al-Academy, 2017)
Despite the artistic importance that Assumption intertextuality in technical studies, it is indispensable for the artist and writer whatever, Intertextuality s is not a coincidence, is not correct to be so, so that human culture is governed by Trait obstetrics and conclusion shows and the longer the life of culture, whatever it be more fortunate the correlation between the present and the past. From this point the problem of current research was founded in the detection of overlapping contexts in contemporary art between intertextuality and quotation, and concluded by identifying the most important terms in the search, while the second chapter highlighted the intertextuality in contemporary artistic discourse and the types of intertextuality and its mechanisms, while the third quarter included measures Search and appointed, the researcher has reached a number of conclusions, including:1. subject Intertextuality figure in the contemporary artwork of the mechanism in the overall analysis of the recalled texts and then re-installed the new formulas are dissolved within the artwork structure.2. contemporary artwork on the graphic level of work according to the law of rumination and repetition on the level of form sometimes, and on the level of content in other times